Preparation method of high-hardness and high-thermal-conductivity copper-based composite material
Through the ball milling and discharge plasma sintering process of Cu powder and TiN powder, the problem of degradation of thermal conductivity when improving strength is solved in traditional copper alloy materials, and a copper-based composite material with high hardness and high heat conductivity is prepared, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411485356.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional copper and its alloy materials will reduce thermal conductivity when increasing strength, making it difficult to take into account high strength, high hardness and good thermal conductivity. The existing copper-based composite preparation methods have problems of thermal conductivity and electrical conductivity.
Cu-TiN composite material is prepared by ball milling Cu powder and TiN powder and undergoing discharge plasma sintering. Specific process conditions such as temperature, time and pressure are used to ensure uniform distribution of TiN, improve the hardness and tensile strength of the material, while maintaining excellent results. electrical and thermal conductivity.
The prepared copper-based composite material has high hardness and tensile strength, and maintains good electrical and thermal conductivity. It is suitable for industrial production of materials such as sizing tubes, and its performance is better than traditional methods.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-based composite material preparation, and in particular relates to a method for preparing a high-hardness and high-thermal-conductivity copper-based composite material. Background Art
[0002] Copper and its alloys have excellent thermal conductivity and electrical conductivity, so they are widely used in heat dissipation, electronic packaging, resistance welding electrodes and other fields. With the development of modern science and technology, the requirements for tensile strength, wear resistance, thermal conductivity and electrical conductivity of materials in various fields are constantly increasing, and traditional copper and its alloy materials are difficult to meet these performance requirements. In order to improve the strength of copper alloys, current research and development is mainly carried out from two aspects: adjusting the type and content of alloy elements and improving the alloy heat treatment process. However, improving the strength of copper alloys will cause its thermal conductivity and electrical conductivity to decrease significantly, and the two cannot be taken into account. Therefore, under the premise of ensuring good thermal conductivity and electrical conductivity, it is an urgent problem to improve the strength and hardness of copper and its alloys. It is of great practical significance to develop a copper and its alloy material with high strength, high hardness, high thermal conductivity and high electrical conductivity.
[0003] In the field of traditional alloys, the introduction of other metal elements will lead to a decrease in thermal conductivity and electrical conductivity of copper alloys, and at high temperatures, due to problems such as grain boundary softening, the strengthening mechanism is difficult to fully exert. Therefore, it is an effective method to prepare copper-based composite materials by combining metal copper with high-performance reinforcement phases and introduce a second phase at the grain boundary to solve the above performance problems. Currently, the widely used methods for preparing copper-based composite materials include powder metallurgy, mechanochemical method, self-propagating high-temperature synthesis method and internal oxidation method, among which powder metallurgy can prepare high-purity materials with low production cost, and is a process method that can be used for mass production. At present, the main ceramic particle reinforcement phases include carbides (such as SiC, TiC, NbC, WC, TaC, etc.), oxides (such as Al2O3, Y2O3, SiO2, Cr2O3, TiO2, etc.), borides (such as TiB2, ZrB2, etc.), diamond particles, carbon fibers, etc. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a method for preparing a copper-based composite material with high hardness and high thermal conductivity. The copper-based composite material prepared by the method has high hardness and tensile strength.
[0005] The present invention provides a method for preparing a high-hardness and high-thermal-conductivity copper-based composite material, comprising the following steps:
[0006] Ball milling Cu powder and TiN powder to obtain Cu-TiN composite powder;
[0007] The Cu-TiN composite powder is ground and sieved and then spark plasma sintered to obtain a copper-based composite material; the spark plasma sintering temperature is 758-763° C. and the time is 4.5-5.5 minutes.
[0008] The present invention only needs raw materials Cu powder and TiN powder to prepare composite powder with uniform distribution of Cu and TiN. After grinding and sieving, a dense copper-based composite block can be prepared by spark plasma sintering under specific conditions.
[0009] The purity of the Cu powder in the present invention is 99.7%, and the average particle size is less than 50 μm; the purity of the TiN powder is 99.9%, and the average particle size is less than 5 μm.
[0010] The mass ratio of the Cu powder to the TiN powder in the present invention is 88 to 92:8 to 12. In a specific embodiment, the mass ratio of the Cu powder to the TiN powder is 92:8, 90:10 or 88:12.
[0011] The present invention puts Cu powder and TiN powder into a WC ball milling jar for ball milling; the ball milling uses a WC ball mill; the diameter of the WC ball mill is 10-15 mm; the mass ratio of the WC ball mill to the mass ratio of the raw material is 9.5-10.5:1; in a specific implementation, the mass ratio of the WC ball mill to the mass ratio of the raw material is 10:1. The rotation speed of the ball milling in the present invention is 150-250 rpm, and the ball milling time is 10-25 hours.
[0012] After obtaining the Cu-TiN composite powder, the present invention grinds and sieves the Cu-TiN composite powder and then performs spark plasma sintering to obtain a copper-based composite material.
[0013] The invention grinds the Cu-TiN composite powder; the mortar used is an alumina mortar; the grinding time is not less than 30 minutes; and the mesh number of the sieve used for sieving is 100 meshes.
[0014] The sieved powder is poured into a graphite mold, and the two ends are pre-pressed with graphite pressure heads and then placed in a spark plasma sintering furnace for sintering; the diameter of the graphite mold used in the present invention is 15 mm; the mass of the Cu-TiN composite powder after grinding and sieving is 10 to 15 g. In the present invention, carbon paper is preferably placed before placing in the mold to facilitate demoulding after sintering.
[0015] In the present invention, the spark plasma sintering is carried out under a vacuum atmosphere with a pressure of 30 to 40 MPa applied throughout the process. The temperature of the spark plasma sintering in the present invention is 758 to 763°C, and the time is 4.5 to 5.5 min. The heating rate of the present invention to the temperature required for spark plasma sintering is 95 to 105°C / min, preferably 98 to 102°C / min; in a specific embodiment, the heating rate is 100°C / min. The temperature measuring device in the present invention is a thermocouple, which makes the temperature measurement in the furnace more accurate.
[0016] The copper-based composite material prepared by the present invention is a dense block, which has excellent mechanical properties such as hardness and strength, and good electrical and thermal conductivity, so that it can be applied to the industrial production of materials such as sizing pipes.
[0017] The process provided by the present invention is a powder metallurgy process, in which no other impurities are introduced in the material production, and the sintering is carried out in a vacuum atmosphere, which does not form pollution, and the obtained product has high purity. The copper-based composite material prepared by the present invention has excellent mechanical properties and good electrical and thermal conductivity, so that the present invention can be applied to the industrial production of materials such as sizing tubes.
[0018] The present invention adopts GB / T 4340.1 to test the hardness of the copper-based composite material; the present invention adopts GB / T228.1-2010 to test the tensile strength of the copper-based composite material; the present invention adopts ASTM C177 to test the thermal conductivity of the copper-based composite material; the present invention adopts GB / T 32791-2016 to test the electrical conductivity of the copper-based composite material.
[0019] The present invention provides a method for preparing a high-hardness and high-thermal-conductivity copper-based composite material, comprising the following steps: ball-milling Cu powder and TiN powder to obtain Cu-TiN composite powder; grinding and sieving the Cu-TiN composite powder and then performing spark plasma sintering to obtain a copper-based composite material; the temperature of the spark plasma sintering is 758-763°C and the time is 4.5-5.5 min. The copper-based composite material prepared by the present invention through the above process has uniform TiN distribution, so that the hardness and tensile strength are improved, and the electrical and thermal conductivity are good, so that it can be used in the industrial production of materials such as sizing pipes. Experimental results show that the hardness of the copper-based composite material is 101H. V ~142H V , strength is 285MPa~384MPa, thermal conductivity is 294W / m·K~321W / m·K, and electrical conductivity is 75%IACS~82%IACS. DETAILED DESCRIPTION
[0020] In order to further illustrate the present invention, a method for preparing a high-hardness and high-thermal-conductivity copper-based composite material provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0021] Example 1
[0022] (1) Weigh 27g of Cu powder and 3g of TiN powder into a WC ball milling jar, add 300g of a WC ball mill with a diameter of 15mm, and perform ball milling in a planetary ball mill at a speed of 200RPM for 20h to obtain a Cu-10wt%TiN composite powder.
[0023] (2) The Cu-10 wt% TiN composite powder obtained in (1) was poured into an alumina mortar and ground for 30 min, and then passed through a 100-mesh sieve to obtain a sieved Cu-10 wt% TiN powder.
[0024] (3) Weigh 15 g of Cu-10wt%TiN composite powder, pour it into a graphite mold with a diameter of 15 mm, put graphite indenters at both ends for pre-compression, and then put it into a spark plasma sintering furnace. First, vacuum treatment is performed by a mechanical pump. The sintering program is set to heat up to 760°C at 100°C / min, keep warm for 5 minutes, and quickly cool to room temperature after the end of the heat preservation. The sintering process is carried out under vacuum, and a pressure of 35 MPa is applied throughout the process to finally obtain a Cu-10wt%TiN block.
[0025] After testing, the Vickers hardness of the sintered Cu-10wt%TiN composite material reached 138H V , higher than 68H of pure copper V The tensile strength of the material reaches 364MPa, which is higher than the 230MPa of pure copper. The thermal conductivity and electrical conductivity are 311W / m·K and 81%IACS respectively, which are slightly lower than the 386W / m·K and 100%IACS of pure copper.
[0026] Example 2
[0027] (1) Weigh 27.6 g of Cu powder and 2.4 g of TiN powder into a WC ball mill, add 300 g of a WC ball mill with a diameter of 15 mm, and mill in a planetary ball mill at a speed of 200 RPM for 25 h to obtain a Cu-8 wt% TiN composite powder.
[0028] (2) The Cu-8wt%TiN composite powder obtained in (1) was poured into an alumina mortar and ground for 30 min, and then passed through a 100-mesh sieve to obtain a sieved Cu-8wt%TiN powder.
[0029] (3) Weigh 15g of Cu-8wt%TiN composite powder and pour it into a graphite mold with a diameter of 15mm. Place graphite indenters at both ends for pre-compression and place it in a spark plasma sintering furnace. First, vacuumize it with a mechanical pump. Set the sintering program to heat it to 760℃ at 100℃ / min, keep it warm for 5min, and then quickly cool it down to room temperature after the end of the heat preservation. The sintering process is carried out under vacuum and a pressure of 35MPa is applied throughout the process to finally obtain a Cu-8wt%TiN block.
[0030] After testing, the Vickers hardness of the sintered Cu-8wt%TiN composite material reached 101H V , higher than 68H of pure copper V The tensile strength of the material reaches 285MPa, which is higher than the 230MPa of pure copper. The thermal conductivity and electrical conductivity are 321W / m·K and 82%IACS respectively, which are slightly lower than the 386W / m·K and 100%IACS of pure copper.
[0031] Example 3
[0032] (1) Weigh 26.4 g of Cu powder and 3.6 g of TiN powder into a WC ball mill, add 300 g of a WC ball mill with a diameter of 15 mm, and mill in a planetary ball mill at a speed of 200 RPM for 15 h to obtain a Cu-12 wt% TiN composite powder.
[0033] (2) The Cu-12 wt% TiN composite powder obtained in (1) was poured into an alumina mortar and ground for 30 min, and then passed through a 100-mesh sieve to obtain a sieved Cu-12 wt% TiN powder.
[0034] (3) Weigh 15 g of Cu-12wt%TiN composite powder, pour it into a graphite mold with a diameter of 15 mm, put graphite indenters at both ends for pre-compression, and then put it into a spark plasma sintering furnace. First, vacuum treatment is performed by a mechanical pump. The sintering program is set to heat up to 760°C at 100°C / min, keep warm for 5 minutes, and quickly cool to room temperature after the end of the heat preservation. The sintering process is carried out under vacuum, and a pressure of 35 MPa is applied throughout the process to finally obtain a Cu-12wt%TiN block.
[0035] After testing, the Vickers hardness of the sintered Cu-12wt%TiN composite material reached 142H V , higher than 68H of pure copper V The tensile strength of the material reaches 384MPa, which is higher than the 230MPa of pure copper. The thermal conductivity and electrical conductivity are 294W / m·K and 75%IACS respectively, which are lower than the 386W / m·K and 100%IACS of pure copper.
[0036] Comparative Example
[0037] (1) Weigh 27g of Cu powder and 3g of TiB2 powder into a WC ball mill, add 300g of a WC ball mill with a diameter of 15mm, and mill in a planetary ball mill at a speed of 200RPM for 20h to obtain a Cu-10wt%TiB2 composite powder.
[0038] (2) pouring the Cu-10wt% TiB2 composite powder obtained in (1) into an alumina mortar and grinding for 30 minutes, and then passing through a 100-mesh sieve to obtain a sieved Cu-10wt% TiB2 powder;
[0039] (3) Weigh 15g of Cu-10wt%TiB2 composite powder and pour it into a graphite mold with a diameter of 15mm. Place graphite indenters at both ends for pre-compression and place it in a spark plasma sintering furnace. First, vacuumize it with a mechanical pump. Set the sintering program to heat it to 760℃ at 100℃ / min and keep it warm for 5min. After the insulation is completed, quickly cool it down to room temperature. The sintering process is carried out under vacuum and a pressure of 35MPa is applied throughout the process to finally obtain a Cu-10wt%TiB2 block.
[0040] After testing, the Vickers hardness of the sintered Cu-10wt% TiB2 composite material reached 89H V , lower than 138H of Cu-10wt%TiN composite V The tensile strength reaches 456MPa, which is higher than the 364MPa of Cu-10wt%TiN composite material. The thermal conductivity and electrical conductivity are 223W / m·K and 61%IACS respectively, which are lower than the 311W / m·K and 81%IACS of Cu-10wt%TiN composite material.
[0041] It can be seen from the above embodiments that the present invention provides a method for preparing a high-hardness and high-thermal-conductivity copper-based composite material, comprising the following steps: ball-milling Cu powder and TiN powder to obtain Cu-TiN composite powder; grinding and sieving the Cu-TiN composite powder and then performing spark plasma sintering to obtain a copper-based composite material; the temperature of the spark plasma sintering is 758-763°C, and the time is 4.5-5.5 min. The TiN in the copper-based composite material prepared by the above process of the present invention is evenly distributed, so that the hardness and tensile strength are improved, and the electrical and thermal conductivity are good, so that it can be used in the industrial production of materials such as sizing pipes. And the comprehensive performance of the copper-based composite material prepared by this process is better than that of the copper-based composite material prepared by Cu-TiB2 powder. The experimental results show that the hardness of the copper-based composite material is 101H V ~142H V , strength is 285MPa~384MPa, thermal conductivity is 294W / m·K~321W / m·K, and electrical conductivity is 75%IACS~82%IACS.
[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-hardness and high-thermal-conductivity copper-based composite material, comprising the following steps: Ball milling Cu powder and TiN powder to obtain Cu-TiN composite powder; The Cu-TiN composite powder is ground and sieved and then spark plasma sintered to obtain a copper-based composite material; the spark plasma sintering temperature is 758-763° C. and the time is 4.5-5.5 minutes.
2. The preparation method according to claim 1, characterized in that: The heating rate to the temperature required for spark plasma sintering is 95 to 105°C / min.
3. The preparation method according to claim 1, characterized in that: The ball mill used in ball milling is a WC ball mill with a diameter of 10 to 15 mm; The rotation speed of the ball mill is 150-250 rpm, and the ball milling time is 10-25 h.
4. The preparation method according to claim 1, characterized in that: Alumina mortar was used for grinding; The grinding time should not be less than 30 minutes.
5. The preparation method according to claim 1, characterized in that: The mesh number of the sieve used for sieving is 100 mesh.
6. The preparation method according to claim 1, characterized in that: The mass ratio of Cu powder to TiN powder is 88-92:8-12.
7. The preparation method according to claim 1, characterized in that: The spark plasma sintering is carried out in a vacuum atmosphere with a pressure of 30 to 40 MPa applied throughout the process.
8. The preparation method according to claim 1, characterized in that: The Cu-TiN composite powder is ground, sieved and placed in a graphite mold; The diameter of the graphite mold is 15 mm; the mass of the Cu-TiN composite powder after grinding and sieving is 10-15 g.
9. The preparation method according to claim 1, characterized in that: The purity of the Cu powder is 99.7% and the average particle size is less than 50 μm; The purity of the TiN powder is 99.9%, and the average particle size is less than 5 μm.
